Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 11 - Review Exercises - Page 842: 104


True. $\displaystyle \sum_{j=1}^{6}2^j=\displaystyle \sum_{j=3}^{8}2^{j-2}$

Work Step by Step

$\displaystyle \sum_{j=1}^{6}2^j=2^1+2^2+2^3+2^4+2^5+2^6=2^{3-2}+2^{4-2}+2^{5-2}+2^{6-2}+2^{7-2}+2^{8-2}=\displaystyle \sum_{j=3}^{8}2^{j-2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.